The O. Henry prize stories. 2007 - Furman, Laura (New York : Anchor Books, 2007)
A collection of short stories judged to be the best in America and Canada for 2006 presents an outstanding selection of short fiction, along with essays by the three judges and commentary from the twenty prize winners.
Room / William Trevor -- Scent of cinnamon / Charles Lambert -- Cherubs / Justine Dymond -- Galveston Bay, 1826 / Eddie Chuculate -- Gift of years / Vu Tran -- Diarist / Richard McCann -- War buddies / Joan Silber -- Djamilla / Tony D'Souza -- In a bear's eye / Yannick Murphy -- Summer, with twins / Rebecca Curtis -- Mudder tongue / Brian Evenson -- Companion / Sana Krasikov -- A stone house / Bay Anapol -- Company of men / Jan Ellison -- City visit / Adam Haslett -- Duchess of Albany / Christine Schutt -- New kind of gravity / Andrew Foster Altschul -- Gringos / Ariel Dorfman -- El ojo de agua / Susan Straight -- View from Castle Rock / Alice Munro.
"The best stories of the year"--Cover.
"With essays on the story they admire most by jurors Charles D'Ambrosio, Ursula K. Le Guin, Lily Tuck."
O. Henry Memorial Award, 2007.
Keywords: Short stories, American; United States -- Social life and customs -- Fiction